Autistic traits are related to worse performance in a volatile reward learning task despite adaptive learning rates. (February 2021) - Goris, Judith; Silvetti, Massimo; Verguts, Tom; Wiersema, Jan R; Brass, Marcel; Braem, Senne
Recent theories propose that autism is characterized by an impairment in determining when to learn and when not. We investigated this by estimating learning rate in environments varying in volatility and uncertainty. Specifically, we correlated autistic traits (in 163 neurotypical participants) with modelled learning behaviour during probabilistic reward learning under the following three conditions: a Stationary Low Noise condition with stable reward contingencies, a Volatile condition with changing reward contingencies and a Stationary High Noise condition where reward probabilities for all options were 60%, resulting in an uncertain, noisy environment. Consistent with earlier findings, we found less optimal decision-making in the Volatile condition for participants with more autistic traits. However, we observed no correlations between underlying adjustments in learning rates and autistic traits, suggesting no impairment in updating learning rates in response to volatile versus noisy environments. Exploratory analyses indicated that impaired performance in the Volatile condition in participants with more autistic traits, was specific to trials with reward contingencies opposite to those initially learned, suggesting a primacy bias. We conclude that performance in volatile environments is lower in participants with more autistic traits, but this cannot be unambiguously attributed to difficulties with adjusting learning rates. Lay abstract: Recent theories propose that autism is characterized by an impairment in determining when to learn and when not. Here, we investigated this hypothesis by estimating learning rates (i.e. the speed with which one learns) in three different environments that differed in rule stability and uncertainty. We found that neurotypical participants with more autistic traits performed worse in a volatile environment (with unstable rules), as they chose less often for the most rewarding option. Exploratory analyses indicated that performance was specifically worse when reward rules were opposite to those initially learned for participants with more autistic traits. However, there were no differences in the adjustment of learning rates between participants with more versus less autistic traits. Together, these results suggest that performance in volatile environments is lower in participants with more autistic traits, but that this performance difference cannot be unambiguously explained by an impairment in adjusting learning rates.